1990
DOI: 10.1007/bf02390862
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme immunoassay for placental protein 4 (PP4) and its possible diagnostic significance in patients with genital tract cancer

Abstract: We have established an enzyme immunoassay for placental protein 4 (PP4), by using avidin-biotin binding reaction, and set its normal range below 10.9 ng/ml (mean + 2 sigma). Throughout the menstrual cycle, the serum PP4 profile was similar to that of serum progesterone. In the follicular and ovulatory phase, PP4 remained relatively low, with the mean levels of 1.5 ng/ml and 1.8 ng/ml, respectively. In the luteal phase, the mean level was 3.2 ng/ml. In normal pregnancy, serum PP4 levels were low irrespective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Lev els of PP4 correlate with progression or regres sion of disease in patients with malignant gynecological tumors [5,6,[8][9][10]. These latter findings suggest that these tumors may con tain PP4 antigen.…”
Section: Introductionsupporting
confidence: 51%
“…Lev els of PP4 correlate with progression or regres sion of disease in patients with malignant gynecological tumors [5,6,[8][9][10]. These latter findings suggest that these tumors may con tain PP4 antigen.…”
Section: Introductionsupporting
confidence: 51%
“…A recent study [39] showed that uterine malignancy had elevated serum placenta protein 4 (PP4) levels: 48% in endometrial carcinoma and 44% in cervical carcino ma. With malignant ovarian neoplasms the figure was 15%.…”
Section: Placenta Proteinmentioning
confidence: 99%